2020
DOI: 10.1016/j.toxrep.2020.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress and apoptotic effects of copper and cadmium in the zebrafish liver cell line ZFL

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 69 publications
1
2
0
Order By: Relevance
“…However, in SH-SY5Y cells, copper applied alone did not induce an increase in caspase-3 activity, and this effect was not modified in the presence of myricetin. Similar findings, i.e., a copper-induced increase in ROS production accompanied with the suppression of apoptosis, were observed in zebrafish cells exposed to copper [44] and in malignant cells [45]. In P19 neuronal cells, we also failed to detect caspase activation during mild copper-induced neuronal damage [8,19].…”
Section: Discussionsupporting
confidence: 85%
“…However, in SH-SY5Y cells, copper applied alone did not induce an increase in caspase-3 activity, and this effect was not modified in the presence of myricetin. Similar findings, i.e., a copper-induced increase in ROS production accompanied with the suppression of apoptosis, were observed in zebrafish cells exposed to copper [44] and in malignant cells [45]. In P19 neuronal cells, we also failed to detect caspase activation during mild copper-induced neuronal damage [8,19].…”
Section: Discussionsupporting
confidence: 85%
“…In a recent study on ZFL cells, co-exposure of increasing concentrations of Cu 2+ with a constant concentration of Cd 2+ could increase toxicity, whereas lower concentrations of Cu 2+ did not alter intracellular Cd 2+ levels. These results indicate that Cu 2+ might reduce Cd 2+ uptake [ 43 ]. Combining these observations with our findings in the present study, Cd 2+ antagonizes Cu 2+ accumulation via CTR1 in ZFL cells, but the effect is very limited.…”
Section: Discussionmentioning
confidence: 99%
“…However, the upregulation of antioxidant genes can also have negative consequences. Kwok and Chan (2020) found that chronic exposure to copper induced the expression of antioxidant genes, including gstt1a and gsr, in the liver of zebra sh. The authors suggested that prolonged upregulation of antioxidant genes can lead to oxidative stress due to the accumulation of reactive oxygen species.…”
Section: Molecular Studiesmentioning
confidence: 95%